2023
DOI: 10.12659/msm.940635
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Preclinical and Clinical Studies in Support of the Role of Non-Steroidal Anti-Inflammatory Drugs in Dentistry

Abstract: Patient pain is a common problem faced by dentists and oral and maxillofacial surgeons. Craniofacial pain may be caused not only by inflammation in the teeth, but also various oral, facial, and nerve-related diseases, as well as tumors. Non-steroidal anti-inflammatory drugs (NSAIDs) constitute the basis of the analgesic ladder. According to the World Health Organisation (WHO), NSAIDs are the first-line drugs in relieving pain and inflammation of oral conditions. NSAIDs have been used in almost every field of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…As reported above, pain and OFP have warning and protective functions, reducing the effects of the noxious stimuli that trigger some reflex responses from the body to the CNS [90,91].…”
Section: Orofacial Pain and Warning-protective Actionsmentioning
confidence: 89%
See 4 more Smart Citations
“…As reported above, pain and OFP have warning and protective functions, reducing the effects of the noxious stimuli that trigger some reflex responses from the body to the CNS [90,91].…”
Section: Orofacial Pain and Warning-protective Actionsmentioning
confidence: 89%
“…These points determine the clinical multidisciplinary questions that require many specialists in several scientific fields. Furthermore, many studies suggested that it is very important to start pharmacotherapy early enough for improving the local and general conditions of patients [91].…”
Section: Orofacial Pain and Warning-protective Actionsmentioning
confidence: 99%
See 3 more Smart Citations